(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
The problem of financing the expensive software financing will appear in modern classes that need to be used information and communication technologies. Educational organizations will only buy and install a package of a specific software. Teachers and students adapt their work to the conditions that do not allow them to fully realize their possibilities. Is there an alternative curriculum that can easily and quickly prepPiling, quickly apply to its class, and that students can show the beauty of using information technology? This problem is solved using new "cloudy" technologies. Currently, web applications can be an effective assistant in the Web 2.0 learning process.